Bancroft Library. Regional Oral History Office oral history interviews - Bancroft Library. Regional Oral History Office; Bary, Helen Valeska, 1887-1973.; Field, Sara Bard, 1882-1974.; Gordon, Walter, 1894-1976.; Kent, Roger, 1906-1980.; Matthews, Burnita Shelton, 1894-1988.; Paul, Alice, 1885-1977.; Rankin, Jeannette, 1880-1973.; Reyher, Rebecca Hourwich, 1897-1987.; Service, Caroline; Vernon, Mabel; Earl Warren Oral History Project (Bancroft Library); et al.
Typewritten transcripts of oral history interviews accompanied by photographs, copies of correspondence, reports, clippings, and other supplementary material.
Interviews pertaining to California state politics and government, the suffragists, and to the life and career of John S. Service, an American diplomat in China, and his wife, Caroline. Includes interviews from the Earl Warren Oral History Project, the Walter Gordon Oral History Project, the Governmental History Documentation Project with Roger Kent, and the Suffragists Oral History Project with Helen Valeska Bary, Sara Bard Field, Burnita Shelton Matthews, Alice Paul, Jeannette Rankin, Rebecca Hourwich Reyher, Mabel Vernon, and others.
Typescripts from original taped interviews.
Bancroft Library
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Service, John S. -- 1909-1999.; Warren, Earl, -- 1891-1974.; Diplomatic and consular service, American -- China; Diplomats' spouses -- Interviews; Politicians -- California -- Interviews; Suffragists -- Interviews; Labor unions -- California; Women -- Suffrage; California -- Politics and government -- 1850-1950.; California -- Politics and government -- 1951-; China -- Foreign relations -- United States; United States -- Foreign relations -- China